Comparison of Cassava Chips and Winged Bean Tubers with Various Starch Modifications on Chemical Composition, the Kinetics of Gas, Ruminal Degradation, and Ruminal Fermentation Characteristics Using an In Situ Nylon Bag and an In Vitro Gas Production Technique - Narirat Unnawong; Chaichana Suriyapha; Benjamad Khonkhaeng; Sompong Chankaew; Teppratan Rakvong; Sineenart Polyorach; Anusorn Cherdthong (Animals, 2023)
This research assessed the impact of cassava chips (CSC) and winged bean tubers (WBT) with various starch modification methods on the chemical composition, ruminal degradation, gas production, in vitro degradability, and ruminal fermentation of feed using an in situ and in vitro gas production technique. Experimental treatments were arranged for a 2 × 5 factorial, a completely randomized design with two sources of starch and five levels of modification treatments. Two sources of starch were CSC and WBT, while five modification treatments of starch were: no modification treatment, steam treatment, sodium hydroxide (NaOH) treatment, calcium hydroxide (CaOH2) treatment, and lactic acid (LA) treatment. The starch modification methods with NaOH and CaOH2 increased the ash content (p < 0.05), whereas the crude protein (CP) content was lower after treatment with NaOH (p < 0.05). Steam reduced the soluble fraction (a) and effective dry matter degradability of WBT in situ (p < 0.05). In addition, the WBT steaming methods result in a lower degradation rate constant in situ (p < 0.05). The degradation rate constants for the insoluble fraction (c) in the untreated CSC were higher than those of the other groups. Starch modification with LA reduced in vitro dry matter degradability at 12 and 24 h of incubation (p < 0.05). The starch modification method of the raw material showed the lowest pH value at 4 h (p < 0.05). The source of starch and starch modification methods did not influence the in vitro ammonia nitrogen concentrations, or in vitro volatile fatty acids. In conclusion, compared to the CSC group and untreated treatment, treating WBT with steam might be a more effective strategy for enhancing feed efficiency by decreasing or retarding ruminal starch degradability and maintaining ruminal pH.